1996
DOI: 10.1002/etc.5620150419
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of the EPA (kenaga) nomogram, a method for estimating wildlife exposure to pesticide residues on plants

Abstract: Abstract-The Kenaga nomogram was developed by the U.S. Environmental Protection Agency (EPA) in the mid 1970s and has since been used prior to the registration of a pesticide to estimate the maximum potential pesticide residue level on plant material in the food chain of wildlife. The objective of this study was to evaluate the nomogram using field data. Six pesticides representing a variety of pesticide classes were applied to 15 plant species. Five of the six nomogram categories were tested with plant parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…For many years estimates of residues on vegetation used in initial tiers of environmental risk assessment have been based on simple empirically derived relationships between application rate and residue levels (Hoerger and Kenaga 1972;Fletcher et al 1994;Pfleeger et al 1996). It is assumed that provided the interval between application and measurement is short, the measured residues provide a good measure of the volume of spray intercepted by the part of the plant that is of interest when normalized for application rate.…”
Section: Dissipation Rate Constant (K)mentioning
confidence: 99%
“…For many years estimates of residues on vegetation used in initial tiers of environmental risk assessment have been based on simple empirically derived relationships between application rate and residue levels (Hoerger and Kenaga 1972;Fletcher et al 1994;Pfleeger et al 1996). It is assumed that provided the interval between application and measurement is short, the measured residues provide a good measure of the volume of spray intercepted by the part of the plant that is of interest when normalized for application rate.…”
Section: Dissipation Rate Constant (K)mentioning
confidence: 99%
“…The assumption underlying the concept of RUD, that residues on plants are proportional to the dosage of pesticide, is supported in 36 of 41 studies in which this could be tested, but as much variance is unexplained as is explained by the linear model. Pfleeger et al [14], who evaluated five of the nomogram categories by spraying pesticides on 15 crop species, concluded that a quadratic model was always a better fit for the relationship between application rate and residue concentration. The discrepancy between the two results may come from the fact that the authors used six rates to test their model, whereas the studies reported here rarely tested more than three application rates.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive use and importance of the nomogram in making regulatory decisions, few efforts have been made to validate this approach. Some studies examining the ability of the nomogram to predict correctly the residues on alfalfa [12,13] and other crops [14] show that residues occasionally exceed the original upper limit values. Of greater relevance, however, is testing the validity of the concept of RUD, because this is the basis for extrapolation of expected environmental concentrations across different application rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EC guidance reviews recent work on estimating residues on vegetation and insects (Luttik, 1992;Fletcher et al, 1994;Pfleeger et al, 1996;Brewer et al, 1997;Fischer and Bowers, 1997;Edwards, 1998;Joerman, 1998). In the past the majority of data concern pesticide residues on plants and residues on insects have been derived from these.…”
Section: Residues On Insectsmentioning
confidence: 98%